LAND REFORM AND CHANGING AGRARIAN LABOUR PROCESSES IN ZIMBABWE - Chambati, Walter Spear Simbarashe (My University, 2011)
This study examines the transformation of the agrarian employment in the former largescale commercial farming sector (LSCF) after the implementation of the Fast Track Land Reform Programme (FTLRP) by the government of Zimbabwe that redistributed over 80 percent of the farms to mostly landless peasants from the communal areas. The key question posed is whether the transfer of land from the former large-scale commercial farmers has created or inhibited opportunities for rural labour to gain incomes and/or livelihoods through self employment as own agricultural producers or in paid wage work. The study was based on a questionnaire survey administered in newly resettled households in Zvimba District and secondary data sources. Various statistical tools were utilised to answer the study’s research questions. Firstly, descriptive statistics were used to characterise the forms of labour that have emerged in the newly resettled areas. Secondly, the Analysis of Variance (ANOVA) test was used to examine the differences in the labour utilisation across the different farm sizes allocated under the FTLRP. Lastly the Chi-Square test was used to relate different factors which were thought to affect the utilisation of labour in newly resettled areas. The study found that FTLRP has been accompanied by the degree of self employment as own producers among newly resettled households in the former wage labour market, although some hired in labour. Hired labour was dominated by casual workers. In comparison to the past scenario the size of the agricultural employment had increased, but new and former farm workers earned unviable wages and benefits and were thus less protected than those in other LSCF subsectors. There was also underutilisation and loss of skills of former farm workers employed in the former LSCF sector. Larger farms with access to capital equipment such as tractors tended to use more absolute hired labour and permanent workers per unit of cropped area, whilst the smaller farms utilised more family and casual labour per unit of cropped area. Across the small and large farms in newly resettled areas, labour use per unit of cropped area was higher compared to the former LSCF sector. In conclusion the land reform programme has the potential to generate employment and thus solve the growing unemployment problem in Zimbabwe, but the capacity of new farmers has to be enhanced to fully utilise their land which is still below its potential through the resolution of production constraints that include finance, skills, input shortages and extension services.
MM - P&DM
Keywords: Land reform - Zimbabwe; Agrarian policies - Zimbabwe